Tectonic controls on active deformation and landscape evolution in the Amanos Mountains along the Duzici-Iskenderun Fault Zone, Eastern Anatolian Fault System - Akgun, Elif; Softa, Mustafa; Irfan, Mohammad; Topal, Savas (Sage Publications Ltd, 2026)
The Duzi & ccedil;i-& Idot;skenderun Fault Zone (DIFZ), located within the Amanos Mountains at the intersection of the African, Arabian, and Anatolian plates, is a structurally segmented and tectonically active component of the Eastern Anatolian Fault System (EAFS). This study integrates morphotectonic analysis, paleoseismological reevaluation, and limited field observations to elucidate the DIFZ's role in deformation patterns and seismic potential. Morphotectonic analysis reveals spatial variability in uplift and erosion, with heightened tectonic activity in basins 4, 9-11, and 18, linked to structural complexities such as fault step-overs, bends, and abrupt topographic changes, suggesting localized strain concentration and elevated seismic potential. Field observations corroborate these findings, documenting triangular facets, V-shaped valleys, elongated basins, and fault scarps indicative of active crustal deformation. Paleoseismological raw data, taken from previously conducted studies at the Elbeyli (Duzi & ccedil;i) and Cona (Osmaniye) sites, identify three surface-rupturing events in the past similar to 12 ka, with Bayesian-derived recurrence intervals of 4.3-4.7 kyr and interevent times of 0.3-9.1 kyr. Magnitude estimates (Mw <= 6.7) and slip rates (<1 mm/yr) classify the DIFZ as a moderately active fault zone. However, limited paleoseismic data from the Erzin and Payas segments constrain comprehensive hazard assessments. These findings highlight the DIFZ as a tectonic linkage between the EAFS, Dead Sea Fault, and Cyprus Arc, facilitating strain transfer across the southeastern Anatolian orogenic front. The integration of morphometric and paleoseismological approaches offers a refined framework for assessing seismic hazards in this tectonically complex region.
Keywords: D & uuml;zi & ccedil;i-& Idot;skenderun Fault Zone; East Anatolian Fault System; morphometric indices; active tectonics; Amanos Mountains